Producción, acame y precocidad en época seca de seis variedades de maíz (Zeamays) en la zona de Fumisa. Quevedo - Alcívar Mendoza, Wilson Dayan (2013)
This work was done in the area belonging to the canton Fumisa Valencia. Province of Los Ríos. The geographical reference 0 ° 31 ' 39'' north latitude and 79 ° 27 ' 53'' West longitude, located 100 meters above sea level, with a duration of four months. Was used a total of 24 plots. It employed a randomized complete block ( DBCA ) with 6 varieties and 4 replicates per variety, with 1 plot ( 6.4m/10m ) by repetition. General objective was raised Evaluate production, earliness and lodging in the dry season of six varieties of maize ( Zea mays ) Fumisa area. For the variable stem diameter is greater in T1 ( Variety 30F35 ) with 1.89cm, this treatment also had the highest moisture 29.11 % , also did not show rollover conjunction with treatment T6 ( Variety PAC105 ). Treatment T3 ( Variety P4226 ) obtained the highest percentage of tipping 0.88 % more weight and diameter of the cob gopher 55.95g and 3.26cm; variables in rows per ear and grains per ear T4 treatment ( Variety DK7088 ) shows the highest values rows 544.15 and 17.94 grains/cob, this same treatment had the highest yield per plant 205.82g and yield per ha-1 167.84qq/ha-1. Also the largest total income, the higher cost and the best cost / benefit with $ 54.14, $ 63.74, and -0.15, respectively. Treatment T5 ( Variety DK399 ), is better in plant height, ear insertion height and number of ears per plot with averages of 2.5m, 1.32m, and 24.96 pods / plot, in the length of 18.61cm gopher, and had the lowest moisture 27.59 %, the ratio grain / gopher is statistically superior to the other treatments T6 ( Variety PAC105 ) with 4.75cm . Keywords: Variety, production, earliness, lodging, dry season.